Mise À Jour De La Cartographie Géologique Et États Des Contraintes Tectoniques Dans La Zone De Bouchfâa (NW Du Massif De Tazekka, Maroc) - Gharmane, Youssef; Fartati, Mohamed El; Amrani, Samir; Hinaje, Saïd (European Scientific Journal, ESJ, 2018)
The tectonic and microtectonic analysis of the Paleozoic and MesoCenozoic series of the Bouchfâa zone (NW of Tazekka) enabled us to highlight tectonic palaeo-stress of essentially compressive stresses. These played a key role in the uprising of the Tazekka Massif. The age and chronology of these paleo-stress are established by analogy with the results obtained in the Middle Atlas, Saïs and High Moulouya. The N165 major compressive phase of post-Bathonian and ante-Barremianage, responsible for the thrust of Lower Lias deposits with those of Middle Lias. The second major compressive episode is oriented N120 in the Vallesian and N140 in the lower Pliocene. These last two tectonic events are responsible for the formation of a ramp-flat system and strik-slep thrust oriented N20 to N70. They affect the paleozoic base of the Tazekka massif and its cover.